PENGARUH INFLASI DAN PRODUK DOMESTIK BRUTO (PDB) TERHADAP SURAT BERHARGA SYARIAH NEGARA (SBSN) 2011-2018 - Akhmad Sobrun Jamil (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2019)
State Sharia Securities (SBSN) or commonly referred to as state sukuk is one of the sharia investment instruments that serves as one of the main sources of state infrastructure financing. This research was conducted with the aim to determine the effect of inflation variables and Gross Domestic Product (GDP) on Government Sharia Securities (SBSN). This study uses time series data from 2011 to 2018 by using multiple linear regression analysis methods and using the Ms. program. Excel 2007 and SPSS 18 to obtain detailed results regarding the relationship between one variable with another variable. The results showed that partially from the T test results, the inflation variable did not affect the State Sharia Securities (SBSN) while the Gross Domestic Product (GDP) affected the State Sharia Securities (SBSN). Simultaneously the results of data processing from the F test results that inflation and Gross Domestic Product (GDP) affect the State Sharia Securities (SBSN). From the R Square test (R2) inflation and Gross Domestic Product (GDP) have a 70.9% effect on the State Sharia Securities (SBSN) while the remaining 29.1% is influenced by other variables not included in this research model